Seleção de traçadores e deriva nas aplicações foliares de produtos fitossanitários na cultura do café (Coffea arábica L.) - Alves, Guilherme Sousa (2014)
Pesticide drift is a serious agricultural problem that is especially significant for perennial crops. Most studies use tracers to quantify pesticide drift. Nevertheless, in Brazil, consensus is lacking on which tracer is the most effective. Thus, given the importance of coffee crops in Brazil, we evaluated several tracers used in application efficiency assessments. We also quantified the drift in coffee crops from hollow cone nozzles with and without air induction and then compared the results with European drift simulation models. We tested Brilliant Blue, Blankophor, Sodium Fluorescein, Rhodamine B and Brilliant Sulfoflavine tracers by evaluating surface tension, hidrogenionic potential, filter paper extraction, sunlight stability and agitation stability. Drift evaluation was based on the ISO 22866 standard. The experiment was set up in randomized blocks with 10 replications in a 2 x 20 split plot consisting of two nozzle types and twenty lines spaced 2.5 m apart and parallel to the target crop row. The spray was a mixture of water and Rhodamine B fluorescent dye at 100 mg L-1. The spray was applied at 400 L ha-1 using a hydro-pneumatic sprayer. Viscosity was similar for all tracers. Brilliant Sulfoflavine had the highest extraction efficiency, whereas Brilliant Sulfoflavine and Brilliant Blue were the most stable in sunlight. Blankophor had the least agitation stability and Brilliant Sulfoflavine was the most appropriate for spray deposition and drift assessment. Rhodamine B was the best option for filter paper targets among low-cost tracers available in Brazil. The air induction nozzle reduced drift to 20 m from the treated area; however, both nozzles produced the same drift within this limit. The drift models behaved differently and did not accurately estimate drift near the target row.